Validated UHPLC-HRMS method for simultaneous quantification of six saponins from the roots of the wild spinach (Chenopodium bonus-henricus L.) - Zlatina Kokanova-Nedialkova; Paraskev Nedialkov (Pensoft Publishers, 2021)
An UHPLC-HRMS method for simultaneous quantification of six saponins from the roots of Chenopodium bonus-henricus L. was developed and validated. All calibration curves showed very good linear regressions and the correlation coefficients were R2 > 0.99. The limits of detection and quantitation limits ranged from 0.20 to 0.61 ng/mL and from 0.61 to 1.85 ng/mL, respectively. A good agreement between the spiked and determined concentrations indicated acceptable accuracy. Besides, the related compounds showed overall recoveries ranging from 95.38% to 103.47% with RSD ranging from 0.64% to 4.25%. The intra-day and inter-day precision were determined by analyzing the retention times and recovery of the calibrants. The saponins of medicagenic acid (3), 2β-hydroxygypsogenin (4), and bayogenin (2) were the predominant compounds and reached 15.01%, 3.87%, 2.41% in the crude EtOH extract and 43.69%, 16.16%, 10.07% in the purified EtOH extract, respectively.